Scenario-Based Land Cover and Land Use Change Modeling in Mae Chang Watershed, Lampang Province, Thailand: 10.32526/ennrj/24/20250115 - Vongvassana, Sirasit; Pattanakiat, Sura; Sriratana Tabucanon, Allan; Chiyanon, Theerawut; Nakmuenwai, Pisut; Lawawirojwong, Siam; Boonriam, Warin; Chinsawadphan, Pathomphot; Phutthai, Thamarat (Environment and Natural Resources Journal, 2025)
The Mae Chang watershed is part of the headwaters of the Wang River, located in Lampang Province in Northern Thailand. Resource pressures at forest-agriculture-extractive frontiers make this landscape crucial for studying land-habitat conversion and guiding sustainable land-use planning. Thus, this study interpreted LULC (1989, 2005, 2013, 2021) and projected LULC for 2029 and 2037 under BAU, conservation (CON), and development (DEV) scenarios using TerrSet’s LCM-MLP with local drivers, isolating intervention effects by contrasting CON/DEV (with constraint and incentive (CI) layers) against BAU (no CI). From 1989 to 2021, deciduous forest declined 23.3% (-249.01 km²), from 1,070.41 to 821.40 km² (65.40→50.18% of the watershed; -15.2 percentage points), while field crops increased by 104.7%, perennial crops by 97.3%, mines/pits by 240.8%, and urban areas by 28.8% based on human activity. Sub-model accuracies ranged 53-92%, and validation achieved Kstandard 0.824, Kno 0.861, Klocation 0.893, exceeding the success threshold. The three future scenarios yielded similar projected areas in both 2029 and 2037 but there were location differences. The deciduous forest area in 2029 and 2037 declined by 22.3% and 31.5%, respectively for all scenarios compared with 2021. The CON scenario outperformed BAU/DEV because strict no-conversion constraints in protected forests and restricted area effectively prevent ongoing deforestation, offering a practical simulation-based tool to support and implement land-use policies at local and regional scales. These findings provide a validated, transferable framework that isolates policy effects and supports evidence-based land-use planning in tropical headwatersheds.